Karakteristik Sistem Sosial Masyarakat Petani Nilam di Aceh Jaya - Agung Prastio; Elly Susanti; Mujiburrahmad Mujiburrahmad (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
Aceh Jaya is on of the most potential region on patchouli commodity development based on plant characteristic which has better quality rather than other regions in Aceh, however until this day the production of patchouli oil on this region still has low productivity and could be upgraded. The characteristics of social system in patchoulis farmer have contribution on social development that has been done on this region. The purpose of this research is to see the characteristics of social system in patchouli’s farmers based on social relation, knowledge, and the norms of corporation among patchouli’s farmer. This research used questionnaire and interview, and observation as technique to collect data. Data that have been collected were analyzed using descriptive analysis method and served on frequent table and radar chart. The result shows that based on 3 elements in social system, farmers still have problem on applying the norm of corporation. Farmers’ social relations are still limited on non-formal relationships with their own community and do not have good coorperation with stakeholders that have an effect on improving farmers’ welfare yet. Farmers’ knowledge still influenced by their ancestral belief and are still relucant to accept updates in patchouli cultivation innovations in Good Agricultural Practice (GAP).